Small-molecule inhibitor LF3 restrains the development of pulmonary hypertension through the Wnt/β-catenin pathway. (19th August 2021) - Lei, Yong; Yang, Qi; Nie, Yongmei; Wan, Juyi; Deng, Mingbin
Abstract: Pulmonary hypertension (PH) associated with congenital heart disease is a progressive hemodynamic disease that can lead to increased pulmonary vascular resistance, vascular remodeling, and even right heart failure and death. LF3 is a novel inhibitor of the reporter gene activity of β-catenin/TCF4 interaction in the Wnt/β-catenin signal pathway. However, whether this action of LF3 can prevent PH development remains unclear. In this study, we investigated the therapeutic effect of LF3 in rat primary pulmonary artery smooth muscle cells (PASMCs) of the PH model. We found that LF3 inhibited the decrease in pulmonary artery acceleration time and ejection time by ultra-high-resolution ultrasound imaging and blocked the increase of pulmonary artery systolic pressure by using the BL420 biological function experimental system and right ventricular hypertrophy index by the electronic scales. Simultaneously, it prevented the increase of α-smooth muscle actin and fibronectin and the decrease of elastin in pulmonary arteries of rats in the PH group, as revealed by an immunohistochemical analysis. Moreover, cell proliferation and migration assays showed that LF3 significantly reduced the proliferation and migration of PASMCs. Western blotting and quantitative real-time polymerase chain reaction analyses revealed that LF3 suppressed the expression of proliferating cell nuclear antigens and Bcl-2 and increased the expression of Bax but did not alter the expressions of β-catenin and TCF4. Taken together, LF3 can reduce the migration and proliferation of PASMCs and induce their apoptosis to prevent the development of PH. It would be worthwhile to explore the potential use of LF3 in the treatment of PH.